Industrial neighborhoods in desert cities: Designing urban landscapes to reduce sandstorm effects in Mussafah - El Amrousi, M.; Elhakeem, M.; Paleologos, E. K. (Frontiers in Built Environment, 2023)
Labor housing projects in many Gulf countries are located in less favorable sites in the desert hinterland. They are characterized by grid-based compositions, simple facades, block buildings positioned on the outskirts of the cities. This development type was implemented in the industrial sector of Abu Dhabi, known as Mussafah. Gradually, this industrial area redeveloped its urban fabric by transforming many of its buildings into mixed-use structures with small gardens that provide open air spaces to the community and promote social interaction. Interventions from the community via introducing small gardens stock increased the sense of belonging, improved the urban fabric and reduced sand movement in the area. ‎ This is important in the Gulf region’s desert environment which gives rise to sandstorms. This study evaluates the amount and distribution of sand around a selected group of buildings in the Mussafah area through experimental work using an environmental wind tunnel. The experiments have shown that adding a fence around the small gardens of the buildings in Mussafah reduced the sand pollution effects significantly.